Risk Selection and Benefits in the Medicare+Choice Program - Feldman, Roger (CENTERS for MEDICARE & MEDICAID SERVICES, 2003)
We estimate the relation between enhanced benefits offered by the Medicare+Choice (M+C) plan in 1999 and a measure of risk selection based on inpatient encounter data. Higher risks are attracted to plans that offer outpatient drug coverage. The risk score increases by 2.2 percent for drug coverage with an annual limit less than $800 and by 3.6 percent for coverage with a limit more than $800. However, some benefits such as dental coverage were related to favorable risk selection. If M+C plans competed on the basis of benefits and premiums, as they would if they could give untaxed premium rebates, benefits that attract high risks would be underprovided.